2007
DOI: 10.1183/09031936.00053607
|View full text |Cite
|
Sign up to set email alerts
|

ExperimentalPseudomonas aeruginosapneumonia: evaluation of the associated inflammatory response

Abstract: An abnormal inflammatory response (IR) in pneumonia is associated with poor outcomes and high mortality. Animal models could help to better understand the relationship between the pulmonary infection and the associated IR. The aims of the present study were to validate an experimental model of pneumonia induced by the inoculation of Pseudomonas aeruginosa in ventilated piglets and to study the associated IR over a long period of time (96 h).Five Lagerwhite-Landrace piglets were ventilated for 4 days. After int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 24 publications
3
30
2
Order By: Relevance
“…methylprednisolone 0.5 mg?kg -1 every 12 h; CIP+GC group). In keeping with the present research protocol, piglets of each group were under mechanical ventilation for 84 h [28]. Piglets that died in the first 12 h were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…methylprednisolone 0.5 mg?kg -1 every 12 h; CIP+GC group). In keeping with the present research protocol, piglets of each group were under mechanical ventilation for 84 h [28]. Piglets that died in the first 12 h were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…The piglets were then placed in a prone position and were mechanically ventilated for 4 days. Ventilator parameters consisted of tidal volume (VT) of 10 mL?kg -1 , a respiratory frequency of 15 breaths?min -1 , an inspiratory time of 33%, with an inspiratory oxygen fraction (FI,O 2 ) of 100% and a positive end-expiratory pressure of 0, as described previously [28].…”
Section: Animal Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies concerning severe pneumonia have shown that, despite the inflammatory response initially being compartmentalised [9], an increase in inflammatory cytokine levels in serum is also detected and related to poor prognosis [10][11][12][13].…”
Section: Inflammatory Response Associated With Pneumoniamentioning
confidence: 99%
“…Although the intimal mechanisms by which the inflammatory response modulated by GCs can interfere with pulmonary infection are not well elucidated, in vitro studies and experimental work in animals have provided some clues regarding this issue. The present authors' group has developed an experimental model of Pseudomonas aeruginosa pneumonia in ventilated pigs [10], in which the effect of GCs has been studied by comparing three groups of animals with severe pneumonia (those without treatment, those with antibiotic treatment and those with antibiotic treatment plus GCs). In this model, pigs treated with antibiotics plus GCs experienced, after 96 h of pneumonia onset, a decrease in the local inflammatory response compared to the other groups.…”
Section: Role Of Glucocorticosteroids In Severe Pneumoniamentioning
confidence: 99%